An annotated catalogue of the Iranian Euphorinae, Gnamptodontinae, Helconinae, Hormiinae and Rhysipolinae (Hymenoptera: Braconidae) - Gadallah, Neveen S.; Ghahari, Hassan; Achterberg, Kees Van (Zootaxa, 2016)
The Iranian species diversity of five braconid subfamilies, Euphorinae (54 species in 16 genera and 8 tribes), Gnamptodontinae (4 species in 1 genus and 1 tribe), Helconinae (9 species in 5 genera and 2 tribes), Hormiinae (8 species in 4 genera and 2 tribe) and Rhysipolinae (3 species in 2 genera) are summarized in this catalogue. A faunistic list is given comprising both local and global distribution of each species under study as well as host records. In the present study ten new records are added to the Iranian fauna: Centistes (Ancylocentrus) ater (Nees), Centistes cuspidatus (Haliday), Meteorus affinis (Wesmael), Meteorus rufus (DeGeer), Microctonus brevicollis (Haliday), Microctonus falciger Ruthe, Peristenus nitidus (Curtis) (Euphorinae), Aspicolpus carinator (Nees), Diospilus capito (Nees) and Diospilus productus Marshall (Helconinae s.l.). Euphorus pseudomitis Hedwig, 1957 is transferred to the subfamily Hormiinae and Hormisca pseudomitis (Hedwig, 1957) is a new combination.